1978
DOI: 10.1111/j.1095-8649.1978.tb04204.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic tracking of the movements of atlantic salmon smolts (Salmo salar L) in the estuaries of two Scottish rivers

Abstract: Ultrasonic telemetry was used to follow the movements of two groups of smolts in the estuaries of two small Scottish rivers. Hatchery reared smolts released into a typical wedge flow, partially mixed estuary had movements which were dominated by the influence of tide on the direction of water flow. The net movements of wild native smolts in a two layer flow estuary, in which freshwater flow dominated, was downstream but were intermittent consisting of short steps and numerous long pauses. The hatchery reared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 4 publications
1
66
1
Order By: Relevance
“…This is of interest because juvenile salmonids form schools during migration (McCormick et al, 1998) and yet for many species this occurs primarily during hours of darkness (e.g. Tytler et al, 1978, but see Soloman, 1978Moore et al, 1995). The results of the smolt experiment contradict previous suggestions that nocturnal migration reflects a passive downstream displacement when dark because fish are either unable to maintain a visual fix on surrounding features (Thorpe et al, 1988 for juvenile Atlantic salmon) or become disoriented (Pavlov, 1994 for subyearling Cyprinidae).…”
Section: Results Outcomes and Observationscontrasting
confidence: 56%
“…This is of interest because juvenile salmonids form schools during migration (McCormick et al, 1998) and yet for many species this occurs primarily during hours of darkness (e.g. Tytler et al, 1978, but see Soloman, 1978Moore et al, 1995). The results of the smolt experiment contradict previous suggestions that nocturnal migration reflects a passive downstream displacement when dark because fish are either unable to maintain a visual fix on surrounding features (Thorpe et al, 1988 for juvenile Atlantic salmon) or become disoriented (Pavlov, 1994 for subyearling Cyprinidae).…”
Section: Results Outcomes and Observationscontrasting
confidence: 56%
“…However, salmonid smolt may actively influence the rate at which they move by swimming (Finstad et al 2005). Some authors have found distinct periodicities, with smolt migrating seaward during the ebb tide, suggesting a passive component to the migration (McCleave 1978, Tytler et al 1978, Aprahamian & Jones 1997, Lacroix et al 2005. Other authors have found evidence of active migration, such as smolt moving against tides (Moore et al 1998) or independently of current direction (Thorstad et al 2004(Thorstad et al , Økland et al 2006.…”
Section: Introductionmentioning
confidence: 98%
“…Telemetry studies have used both wild and hatchery-reared smolt. This distinction is important as hatchery-reared smolt may show different behaviours, and thus different migration patterns, compared to wild smolt (Tytler et al 1978, McCormick et al 1998.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the estuarine phase of the migration is more restricted. However, studies in eastern North America and in Scotland indicate that the seawards movement of juvenile Atlantic salmon within estuaries takes place even when temperatures are well below 10°C, that it is largely passive, occurring during both nocturnal and diurnal flood tides, and that it sometimes occupies only a few days (Fried et al, 1978;McCleave, 1978;Tytler et al, 1978;LaBar et al, 1979;Cunjak et al, 1989).…”
Section: Introductionmentioning
confidence: 99%